2011
DOI: 10.1007/s11418-011-0547-5
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenes involved in the anti-inflammatory effect of ethanolic extract of Pterodon emarginatus Vogel stem bark

Abstract: Bioassay-guided fractionation of the ethanolic extract of Pterodon emarginatus Vogel stem bark (EtEx) resulted in the isolation and characterization of lupeol and betulin. Their structures were elucidated by spectroscopic methods including IR, (1)H-NMR, (13)C-NMR and comparison with literature values. This study showed the anti-inflammatory activity of EtEx, the hexane (HexL) and dichloromethane (DichL) layers, and lupeol and betulin. The extract, HexL, DichL, lupeol and betulin were able to inhibit acetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
1
10
0
3
Order By: Relevance
“…The description of the influence of lupeol and botulin in the anti-inflammatory properties of ethanol extract were also reported. 43 Our results demonstrated the influence of geranylgeraniol in the intensity of anti-inflammatory activity under edematogenic mechanisms. The early phase starts immediately after carrageenan injection and lasts for approximately 6 h, also leads to activation and secretion of mediators that include bradykinin and arachidonic acid metabolites such as prostaglandins and leukotrienes.…”
Section: Discussionsupporting
confidence: 55%
“…The description of the influence of lupeol and botulin in the anti-inflammatory properties of ethanol extract were also reported. 43 Our results demonstrated the influence of geranylgeraniol in the intensity of anti-inflammatory activity under edematogenic mechanisms. The early phase starts immediately after carrageenan injection and lasts for approximately 6 h, also leads to activation and secretion of mediators that include bradykinin and arachidonic acid metabolites such as prostaglandins and leukotrienes.…”
Section: Discussionsupporting
confidence: 55%
“…The oleaginous extract of the seeds also showed antinociceptive and anti-inflammatory properties, which were thought to be attributed to furane diterpene derivatives of vouacapan and non-vouacapan compounds (Coelho et al 2005;Galceran et al 2011). Triterpenes were suggested to be responsible for the anti-inflammatory effect in the extract from the P. emarginatus bark (Moraes et al 2012).…”
Section: Introductionmentioning
confidence: 96%
“…The phytochemical analyses of P. emarginatus showed the presence of terpenoids (furane diterpene derivatives) (Coelho et al 2005;Galceran et al 2011) and phenolic compounds (flavonoids and isoflavones) (Dutra et al 2009) in the fruits and seeds. Flavonoids, saponin heterosides (Bustamante et al 2010) and triterpenes, including lupeol and betulin (Moraes et al 2012), were identified in the bark.…”
Section: Introductionmentioning
confidence: 99%
“…Some flavonoids can block the biosynthetic processes of eicosanoids, which lead to an anti-inflammatory action, because it causes inhibition of COX-2 and nitric oxide synthase (Machado et al, 2008). It is also reported that triterpenes have anti-inflammatory activity, due to inhibition of nitric oxide and prostaglandin E2 synthesis (Moraes et al, 2012). However, other disorders can lead to a decrease in PMNL migration.…”
Section: Discussionmentioning
confidence: 99%